Methanolic extract of Malus domestica mitigates formalin - Induced derangements in small intestinal motility and transit - Oka, Victor Otu; Nna, Victor Udo; Inyang, Ememfon G.; Ikpe, John B. (Asian Journal of Medical Sciences, 2014)
Objective: This study was carried out to ascertain the effect of formalin ingestion on smallintestinal motility and transit, and the impact of treatment with Malus domestica on same. Methodology: Twenty albino wistar rats weighing 180 - 200 g were used for this study.The animals were randomly divided into 4 groups of 5 rats each. Group 1 served as control,group 2 - formalin treated group, group 3 - M. domestica treated group and group 4 - formalintreated group administered with M. domestica. The daily oral dose employed in this studywas 2.5mg/100g and 40mg/100g for formalin and M. domestica respectively. After 21days of treatment, intestinal transit experiment was carried out on the animals and intestinalmotility was also carried out on the isolated rat ileum using graded doses of acetylcholine andatropine. Results: Basal contraction of isolated rat ileum was signifi cantly (p<0.001) lower inthe formalin treated and M. domestica treated group compared to control. It was signifi cantly(p<0.001) higher in Formalin+M. domestica group compared to formalin treated and M.domestica treated group. Formalin+M. domestica group showed a dose dependent increasein contraction of isolated rat ileum when acetylcholine was administered, and a signifi cantly(p<0.001) lower percentage relaxation in response to atropine administration, compared toformalin treated and M. domestica treated group. Small intestinal transit was signifi cantly(p<0.05) reduced in formalin treated and M. domestica treated group, compared to control.It was also signifi cantly (p<0.05) reduced in formalin+M. domestica group compared toformalin treated and M. domestica treated group. Conclusion: Malus domestica reversesformalin induced decrease in small intestinal motility and transit and may be benefi cial intreating constipation occasioned by ingestion of formalin. Asian Journal of Medical Science, Volume-5(3) 2014: 45-50 http://dx.doi.org/10.3126/ajms.v5i3.9106